Mst1-Deficiency Induces Hyperactivation of Monocyte-Derived Dendritic Cells via Akt1/c-myc Pathway - Cho, Kyung-Min; Kim, Myun Soo; Jung, Hak-Jun; Choi, Eui-Ju; Kim, Tae Sung (Frontiers in Immunology, 2019)
Mst1 is a multifunctional serine/threonine kinase that is highly expressed in several immune organs. The role of Mst1 in the activation of dendritic cells (DCs), a key player of adaptive immunity, is poorly understood. In this study, we investigated the role of Mst1 in GM-CSF-induced bone marrow-derived DCs and the underlying mechanisms. Mst1-/- DCs in response to GM-CSF expressed higher levels of activation/maturation-related cell surface molecules, such as B7 and MHC class II than Mst1+/+ DCs. Furthermore, the expression of proinflammatory cytokines, such as IL-23, TNF-α, and IL-12p40, was increased in Mst1-/- DCs, indicating that Mst1-deficiency may induce the hyperactivation of DCs. Additionally, Mst1-/- DCs exhibited a stronger capacity to activate allogeneic T cells than Mst1+/+ DCs. Silencing of Mst1 in DCs promoted their hyperactivation, similar to the phenotypes of Mst1-/- DCs. Mst1-/-DCs exhibited an increase in Akt1 phosphorylation and c-myc protein levels. In addition, treatment with an Akt1 inhibitor downregulated the protein level of c-myc increased in Mst1-deficient DCs, indicating that Akt1 acts as an upstream inducer of the de novo synthesis of c-myc. Finally, Akt1 and c-myc inhibitors downregulated the increased expression of IL-23p19 observed in Mst1-knockdown DCs. Taken together, these data demonstrate that Mst1 negatively regulates the hyperactivation of DCs through downregulation of the Akt1/c-myc axis in response to GM-CSF, and suggest that Mst1 is one of the endogenous factors that determine the activation status of GM-CSF-stimulated inflammatory DCs.